2015
DOI: 10.5301/je.5000231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Activity on Pain Perception in an Animal Model of Endometriosis

Abstract: Background Symptoms of endometriosis, such as pain and infertility, are considered significant sources of stress. In many chronic conditions, exercise can act as a stress buffer and influence pain perception. We tested the impact of swimming exercise on pain perception and pain receptors in an animal model of endometriosis. Methods Endometriosis (Endo) was induced in female rats by suturing uterine horn tissue next to the intestinal mesentery. Sham rats received sutures only. Rats were exposed to swimming ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 53 publications
2
23
0
3
Order By: Relevance
“…The implants that developed into vesicles were excised from the mesentery, weighed and measured using a digital caliper. Classification of vesicles was carried out as previously described [ 26 , 36 ] and assigned the following grades: grade 1 = disappeared; grade 2 = 0.01–1.99 mm; grade 3 = 2–4.49 mm; grade 4 = 4.5–5.99 mm; grade 5 = 6.0 mm or larger. In sham animals, we counted and collected the empty suture sites.…”
Section: Methodsmentioning
confidence: 99%
“…The implants that developed into vesicles were excised from the mesentery, weighed and measured using a digital caliper. Classification of vesicles was carried out as previously described [ 26 , 36 ] and assigned the following grades: grade 1 = disappeared; grade 2 = 0.01–1.99 mm; grade 3 = 2–4.49 mm; grade 4 = 4.5–5.99 mm; grade 5 = 6.0 mm or larger. In sham animals, we counted and collected the empty suture sites.…”
Section: Methodsmentioning
confidence: 99%
“…Three types of behaviors were analyzed: struggling, defined as a rapid movement in which the rat breaks the surface of the water with the forepaws; swimming, defined as horizontal movements across the surface of the water; and immobility defined as the absence of movement, except for those required to breathe and keep the head above the water. Depressive-like behaviors are characterized by an increase in immobility time and a decreased latency for immobility [38]. Behavior was recorded using a video camera located in front of the apparatus and analyzed with AnyMaze Software (Stoelting, Wood Dale, IL).…”
Section: Methodsmentioning
confidence: 99%
“…10 Previous work from our group has demonstrated that stress can exacerbate the progression of endometriosis, 11 but its controllability can have beneficial effects. 12 In the clinical scenario, we and others have also demonstrated that endometriosis/dysmenorrhea causes an adaptive decrease in cortisol secretion once the disease has been established, pointing toward a malfunction of the hypothalamic-pituitary-adrenal (HPA) axis stress system. 13,14 Consequently, women with endometriosis might greatly benefit from alternative interventions that target stress reduction and promote well-being.…”
Section: Introductionmentioning
confidence: 97%